Genetic regulation of variable Vi antigen expression in a strain of Citrobacter freundii. - Snellings, N J (1981)
Certain strains of the genus Citrobacter exhibit a variable expression of the Vi surface antigen that appears to involve a special mechanism for regulation of gene expression. Two nonlinked chromosomal loci, viaA and viaB, are known to determine nonvariable Vi antigen expression in strains of Salmonella. To confirm the presence of analogous loci in Citrobacter and to ascertain whether either of them is involved in variable Vi antigen expression in this organism, donor strains were constructed from Citrobacter freundii WR7004 and used to transfer their Vi antigen-determining genes to ViaA- and ViaB- Salmonella typhi recipient strains. Vi antigen expression in C. freundii was found to be controlled by loci analogous to the Salmonella via genes. S. typhi recipients of the C. freundii viaA+ genes were restored to the full, continuous expression of the Vi antigen normally seen in S. typhi. Thus, the C. freundii viaA genes appeared to play no role in the variable expression of the Vi antigen. In contrast, S. typhi recipients of the C. freundii viaB+ genes exhibited the rapid, reversible alternation between full Vi antigen expression and markedly reduced Vi antigen expression that was seen to occur in the C. freundii parent. The C. freundii viaB locus was thus identified as the one whose genes are regulated so as to produce variable Vi antigen expression. Genes determining another C. freundii surface antigen, the synthesis of which is not affected by the mechanism regulating Vi expression, were coinherited with the C. freundii viaB+ genes. An invertible, insertion sequence element located within the C. freundii viaB locus is proposed to account for the regulation of variable Vi antigen expression.